2018
DOI: 10.1007/s11920-018-0888-9
|View full text |Cite
|
Sign up to set email alerts
|

Launching Anxious Young Adults: A Specialized Cognitive-Behavioral Intervention for Transitional Aged Youth

Abstract: Anxiety disorders are the most common mental health diagnoses among emerging adults, and individuals suffering from these disorders often experience compounding functional impairments across health, financial, and social domains. While evidence-based treatments exist for both child/adolescent anxiety disorders and adult anxiety disorders, no specialized assessment or treatment methods have been established for the unique period of emerging adulthood. Our review examines literature pertinent to anxiety disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Epidemiological surveillance in the United States indicates that emerging adults (ages 18–25) report the highest prevalence of elevated symptoms of depression (13.1%) in comparison to adolescents and all other adult age groups (Substance Abuse and Mental Health Services Administration [SAMHSA], 2018). Although there is little to no nationally representative data on the prevalence of symptoms of generalized anxiety among emerging adults, researchers have indicated that the prevalence of symptoms of anxiety increase from adolescence to emerging adulthood, and anxiety symptoms/disorders, particularly generalized anxiety, are the most prevalent mental health problems that affect emerging adults in the US (Hoffman, Guerry, & Albano, 2018; Kranzler, Elkins, & Albano, 2019; Tanner, 2016). It is hypothesized that emerging adults are at high risk of developing symptoms of depression and anxiety because this life stage is marked with significant life transitions, high levels of instability, and taking on new and challenging developmental tasks (Arnett, 2000; Arnett, Žukauskienė, & Sugimura, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological surveillance in the United States indicates that emerging adults (ages 18–25) report the highest prevalence of elevated symptoms of depression (13.1%) in comparison to adolescents and all other adult age groups (Substance Abuse and Mental Health Services Administration [SAMHSA], 2018). Although there is little to no nationally representative data on the prevalence of symptoms of generalized anxiety among emerging adults, researchers have indicated that the prevalence of symptoms of anxiety increase from adolescence to emerging adulthood, and anxiety symptoms/disorders, particularly generalized anxiety, are the most prevalent mental health problems that affect emerging adults in the US (Hoffman, Guerry, & Albano, 2018; Kranzler, Elkins, & Albano, 2019; Tanner, 2016). It is hypothesized that emerging adults are at high risk of developing symptoms of depression and anxiety because this life stage is marked with significant life transitions, high levels of instability, and taking on new and challenging developmental tasks (Arnett, 2000; Arnett, Žukauskienė, & Sugimura, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance not trying out for a team, expanding a friend group, moving away from home or taking other "healthy risks". Along these lines, recent work frames "failure to launch" (gaining independence from one's parents) as a form of avoidance linked anxiety in the transition to adulthood (Hoffman et al, 2018;Lebowitz, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This could be addressed by programs that teach youth to approach rather than avoid novel situations, and, in parallel, teach parents to support emerging adult independence. Already, developmentally tailored interventions such as the Launching Emerging Adults Program (LEAP; Hoffman, Guerry, & Albano, 2018) are producing encouraging results. Similarly, a clearer understanding of the influence of peer social support on SUDs and depression may highlight how peers may be more leveraged during treatment.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%